2022
DOI: 10.3389/fvets.2022.904667
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Aronia melanocarpa Pomace Supplementation Enhances the Expression of ZO-1 and Occludin and Promotes Intestinal Development in Pigs

Abstract: A fruit juice production byproduct, Aronia melanocarpa pomace (AMP) is rich in natural polyphenol antioxidant components. The objectives of this study were to study the effects of dietary AMP supplementation on the feeding outcome and intestinal barrier function of pigs. In total, 27 growing pigs (Duroc × Landrace × Yorkshire, ~60 days, average weight of 27.77 ± 2.87 kg, males and females included at random) were randomly allotted to 3 treatment groups, with 3 repetitions per group and 3 pigs per repetition. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Commonly, a greater serum TC concentration means a higher risk of cardio-cerebrovascular disease in mammal. Our results showed that the TC was lesser in 1.5% and 2.0% SBP groups and HDL was greater in 2.0% SBP group, which in agreement with a previous study on pig offered Aronia melanocarpa Pomace (Ren et al, 2022). The AST and ALT, as the important indicators that reflect liver damage, were increased as the liver was damaged (Schomaker et al, 2020).…”
Section: Serum Metabolites Indexessupporting
confidence: 92%
“…Commonly, a greater serum TC concentration means a higher risk of cardio-cerebrovascular disease in mammal. Our results showed that the TC was lesser in 1.5% and 2.0% SBP groups and HDL was greater in 2.0% SBP group, which in agreement with a previous study on pig offered Aronia melanocarpa Pomace (Ren et al, 2022). The AST and ALT, as the important indicators that reflect liver damage, were increased as the liver was damaged (Schomaker et al, 2020).…”
Section: Serum Metabolites Indexessupporting
confidence: 92%
“…Additionally, villus height and crypt depth are two common indices used to assess broilers intestinal integrity. Increased villus height indicates increased surface area for nutrient absorption, whereas increased crypt depth indicates rapid tissue turnover, which is typically associated with decreased nutrient digestion and absorption capacity 33 . In this study, the group provided MHA-Zn (90 mg/kg) had a significantly increased ileal villus height and decreased crypt depth in ileum compared with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Here, dietary supplementation with CTC or 10-HDA effectively reduced the LPS-induced elevation of serum DAO levels. Moreover, intestinal tight junction proteins play key roles in the formation of the intestinal selective permeability barrier, contributing to maintaining the integrity of the intestinal structure ( Ren et al, 2022 ). We found that supplementation with CTC or 10-HDA could ameliorate the downregulation of ZO-1 and OCLN expression in the chickens’ jejunum induced by LPS.…”
Section: Discussionmentioning
confidence: 99%